Born to be an entrepreneur? How cultural origin affects entrepreneurship - Katharina Erhardt; Simon Haenni (University of Zurich, Department of Economics, 2018)
Persistent differences in entrepreneurial activity between regions and countries remain unexplained. This paper argues that cultural heritage is an important determinant. We exploit a quasi-experimental setting comparing entrepreneurial activities of individuals with different cultural ancestry from within Switzerland but who live in the same municipality today and are hence exposed to the same economic and institutional environment. We find that individuals with cultural origin on the German-speaking side of the Swiss language border found 20% more firms than their counterparts with cultural origin on the French-speaking side - no matter if they currently live in the German-speaking or French-speaking region. These newly founded firms are identical in terms of survival rate, industry composition, legal form, and firm size, independent of the cultural origin of firm founders. A model of entrepreneurial choice suggests that the empirical patterns of firm entry and performance are more likely driven by differences in risk aversion or preferences for entrepreneurship rather than by skill.
Keywords: D22; L26; Z10; 330; culture; entrepreneurship; natural experiment